The phytochemical and pharmacological profi le of Persea americana Mill - Yasir, Mohammad; Das, Sattwik; M. D., Kharya (Pharmacognosy Reviews, 2010)
Over the past decades, herbal medicine has become a thing of global significance with medicinal and economic implications. Wide spread use of herbs throughout the globe has raised serious concerns over its quality, safety, and efficacy. Thus, exact scientific assessment has become a precondition for acceptance of herbal health claims. Persea americana Mill. (avocado) is a tree, native to central America, cultivated in tropical and subtropical climates around the world, belonging to the family Lauraceae, is widely used in Ayurveda and evidence-based phototherapy. There are 3 principal races or groups of avocado: Mexican, Guatemalan, and West Indian named for the areas where they were originally cultivated. The plant is used in traditional medicine for the treatment of various ailments, such as monorrhagia, hypertension, stomach ache, bronchitis, diarrhea, and diabetes. Peptone, β-galactoside, glycosylated abscisic acid, alkaloids, cellulose, polygalacto urease, polyuronoids, cytochrome P-450, and volatile oils are reported to be present in this plant. Biotechnologic approaches show that modified MS medium supplemented with 1.0 mg benzyladenine/L, 0-1mg Indole Butyric Acid/L, 0.1 mg Gibberalic Acid 3/L was optimum for adventitious shoot development. In the present review, an effort has been made to study the different aspects of P. americana Mill.
Keywords: Antihypertension; glycosylated abscisic acid; lauraceae; persea americana